Dysregulation of hypoxia-inducible factor 1α in the sympathetic nervous system accelerates diabetic cardiomyopathy - Hrabalova, Petra; Bohuslavova, Romana; Matejkova, Katerina; Papousek, Frantisek; Sedmera, David; Abaffy, Pavel; Kolar, Frantisek; Pavlinkova, Gabriela (Cardiovascular diabetology, 2023)
BACKGROUND: An altered sympathetic nervous system is implicated in many cardiac pathologies, ranging from sudden infant death syndrome to common diseases of adulthood such as hypertension, myocardial ischemia, cardiac arrhythmias, myocardial infarction, and heart failure. Although the mechanisms responsible for disruption of this well-organized system are the subject of intensive investigations, the exact processes controlling the cardiac sympathetic nervous system are still not fully understood. A conditional knockout of the Hif1a gene was reported to affect the development of sympathetic ganglia and sympathetic innervation of the heart. This study characterized how the combination of HIF-1α deficiency and streptozotocin (STZ)-induced diabetes affects the cardiac sympathetic nervous system and heart function of adult animals. METHODS: Molecular characteristics of Hif1a deficient sympathetic neurons were identified by RNA sequencing. Diabetes was induced in Hif1a knockout and control mice by low doses of STZ treatment. Heart function was assessed by echocardiography. Mechanisms involved in adverse structural remodeling of the myocardium, i.e. advanced glycation end products, fibrosis, cell death, and inflammation, was assessed by immunohistological analyses. RESULTS: We demonstrated that the deletion of Hif1a alters the transcriptome of sympathetic neurons, and that diabetic mice with the Hif1a-deficient sympathetic system have significant systolic dysfunction, worsened cardiac sympathetic innervation, and structural remodeling of the myocardium. CONCLUSIONS: We provide evidence that the combination of diabetes and the Hif1a deficient sympathetic nervous system results in compromised cardiac performance and accelerated adverse myocardial remodeling, associated with the progression of diabetic cardiomyopathy.
Keywords: sympatický nervový systém; Diabetes Mellitus, Experimental; Collagen deposition; srdce; Sympathetic Nervous System; Diabetic Cardiomyopathies; experimentální diabetes mellitus; myši; Inflammation; Mice; Sympathetic neurons; myokard; Heart; Cardiac function; zvířata; Myocardium; Animals; diabetická kardiomyopatie; Diabetic cardiomyopathy